2016
DOI: 10.1039/c5dt02854j
|View full text |Cite
|
Sign up to set email alerts
|

On the energetics of P–P bond dissociation of sterically strained tetraamino-diphosphanes

Abstract: The homolytic P-P bond fission in a series of sterically congested tetraaminodiphosphanes (R2N)2P-P(NR2)2 ({4}2-{9}2, two of which were newly synthesized and fully characterized) into diaminophosphanyl radicals (R2N)2P˙ (4-9) was monitored by VT EPR spectroscopy. Determination of the radical concentration from the EPR spectra permitted to calculate free dissociation energies ΔGDiss(295) as well as dissociation enthalpies ΔHDiss and entropies ΔSDiss, respectively. Large positive values of ΔGDiss(295) indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 47 publications
4
46
0
Order By: Relevance
“…The observed temperature dependence of the EPR spectra suggests that the radicals 11 recombine at lower temperature and exist in a dynamic equilibrium with the diphosphane. Similar reversible equilibria have precedence for amino‐diphosphanes . Prolonged heating of toluene solutions of 4 under inert conditions affords detectable amounts of secondary phosphane 2 , suggesting that radicals 11 may be irreversibly quenched by hydrogen abstraction, e. g. from the solvent.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The observed temperature dependence of the EPR spectra suggests that the radicals 11 recombine at lower temperature and exist in a dynamic equilibrium with the diphosphane. Similar reversible equilibria have precedence for amino‐diphosphanes . Prolonged heating of toluene solutions of 4 under inert conditions affords detectable amounts of secondary phosphane 2 , suggesting that radicals 11 may be irreversibly quenched by hydrogen abstraction, e. g. from the solvent.…”
Section: Resultsmentioning
confidence: 73%
“…Single crystal XRD studies of 8 and 9 show a twisted arrangement with respect to the P−P bond for 8 , while 9 adopts a nearly antiperiplanar orientation (Figures and ). The P–P distance of the central bond is 2.3019(11) Å for 8 and 2.281(3) Å for 9 , both exceeding the respective bond length in Hittorf's phosphorus but well within the range observed for bulkily substituted tetraamino‐diphosphanes (2.24–2.34 Å). The pyramidal coordination geometry around the phosphorus atoms of 8 (sum of bond angles 313(1)°) is slightly flattened compared to 4 (sum of bond angles 304–308°) and becomes even more planarized in 9 (sum of angles 322(1)°/323(1)°).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Wright and co‐workers showed that readily available diazaphospholene chloride 3‐Cl is reductively coupled to form bis‐diazaphospholene 2 in the presence of magnesium dust (Equation 1, Scheme ) . Bis‐diazaphospholene 2 was shown to be a source of persistent 7 pi radical 5 , however the solution concentration of these radicals is typically low relative to that of dimer 2 at ambient temperature . We found that 2 could be accessed in high yield and purity via reductive coupling of readily accessible 3‐Br with magnesium turnings in THF .…”
Section: Methodsmentioning
confidence: 77%
“…S22†). In computational studies of diphosphines the inclusion of dispersion correction is reportedly critical to the determination of P–P homolytic dissociation energies 35. We have considered dispersion corrections through use of Grimme's DFT-D3 correction36 in PBE1PBE/6-311++G(d,p) optimization and frequency analysis of the phosphinophosphoniums [Et 2 PPMe 3 ] + and [ t Bu 2 PPMe 3 ] + .…”
Section: Resultsmentioning
confidence: 99%